Effects of social cognitive enhancement with family involvement program on game addictive prevention in male junior high school students - Laolam, Pagagrong; Lapvongwatana, Punyarat; Chansatitporn, Natkamol (Chulalongkorn Medical Journal, 2022)
Background: Gaming addiction is addressed in the 11th revision of the International Classification of Diseases (ICD-11) as its high negative effects to personal, family, social, educational, and occupational aspects of adolescents’ life. Objective: This quasi-experimental research aimed to examine positive effects of social cognitive enhancement with family involvement (SCEFI) program on game addictive prevention in male junior high school. Methods: Sixty-two of 8th Grade students were equally assigned into the experimental and comparison groups. The experimental group received the SCEFI program plus one activity of family involvement while the comparison group received routine activities. The study intervention was 7 weeks with 3 times data collection at: before-intervention, immediately after-intervention, and 4 week follow-up. Results: The results revealed that those within the experimental group had significantly higher mean scores of game addiction knowledge, self-regulation in game playing, and game monitor behaviors than those before-intervention (P < 0.001) and also higher than those in the comparison group at immediately after-intervention and at follow-up (P < 0.001). Additionally, those within the experimental group showed significantly lower levels of game addiction at immediately after-intervention and at follow-up than those before-intervention (P < 0.001) and also lower than those in the comparison group at immediately after-intervention and at follow-up (P < 0.001). Conclusion: This program is successfully implemented and should be further suggested to enable the social cognitive thinking of those with addictions to reduce their levels and also to prevent novice students from game initiation.